Occupational safety and health at metal casting company - Arinda Soraya Putri; Usamah Afiq Nuruddin (Faculty of Engineering, Universitas Negeri Yogyakarta, 2022)
A cast metal company has become a vital industrial sector. It creates various kinds of products like cages, souvenirs, kitchen appliances, ashtrays, ship joint shafts, hotplates, fitness equipment, manual water pumps, pendulum scales, garden benches, lamp posts, interior lights, wall lamps, grills, manhole, and other types of equipment to deal with workplace safety. However, some workers ignore the various potential hazards during the production process. They are more concerned with comfort aspects than safety. This research enhances occupational safety and health (OSH) aspects through Hazard Identification Risk Assessment Risk Control (HIRARC). It is done by identifying potential hazards in the workplace and making a hazard risk assessment to determine appropriate controls for reducing the hazard risks. Based on hazard identification and risk assessment, the results show 11 high, 2 medium-risk, and 1 low-risk levels. The risk control proposals are in the form of training on the importance of OSH among employees/workers. It also raises awareness to provide work safety facilities and establish policies related to OSH.